Disorientation and disillusionment in Post-9/11 poetry - Kočan, Kristina (ELOPE (Ljubljana), 2016)
The paper examines the immediate responses that emerged in American poetry after the terrorist attacks on 11 September, 2001. The aim of the paper is not to summarize the tragic events of 9/11, but to show how poets reacted to the terrorist attacks. In response to 9/11, a great deal of poetry emerged that expresses the poetic and completely personal, intimate side of the crisis, and many printed publications appeared in which poets addressed 9/11. Although one can find a range of features in American poetry after the attacks, there are notable similarities among the poetry being produced. The post-9/11 poetry can be divided into thematic clusters. This paper is, however, limited to responses that deal only with feelings of disorientation, loss and despair after 9/11. Furthermore, the paper presents poetic reactions that involve a sense of disillusionment and the idea that everything changed after the attacks. Each thematic cluster offers examples of 9/11 poetry that are interpreted with the help of close reading.
Keywords: 11. september 2001; American literature; ameriška književnost; krize; literarne študije; natančno branje; odzivi; sodobna ameriška poezija; tematske kritike; travme